(untitled) (Journal of Surgical Sciences, 2019)
Background: Hypospadias is the result of failure of fusion of the urethral folds on the ventral aspect of the penis.It usually occur 1 in every 300 male children.Reconstruction of urethra in childhood is the only hope of cure. The aim of this study is to find out the out.come of tubularized incised plate urethroplasty for distal penile hypospadias and to - ow that this procedure will end up in a better cosmetic appearance. Methods: This prospective study was conducted in a private medical college hospital, Comilla between July 2011 to June 2012 on 30 patients using Snodgrass technique of hypospadlas surgery. All cases were consecutively selected. Data were processed and analysed· using software SPSS (Statistical Package for social Sciences) version 11.5 and the test· statistics used to analyse the data were descriptive statistics and Z-test for proportion. The variables studied were age, socioeconomic condition, post-operative complications, such as infection rate, urethrocutaneous fistula, meatal stenosis, wound dehiscence etc. &cosmatic outcome such as size of the meatus, shape of the glans studied. Results: Satisfactory results were obtained in 21 (70%) patients and only 8 (26.67%) had urethrocutaneous fistula, 1(3.33%) had retrusive meatus and 7 (23.33%) had wound infection. The final outcome was evaluated based on urethrocutaneous fistula and cosmesis. Out of 30 patients, 21(70%) did not have urtethrocutaneous fistula and were cosmetically acceptable. Binomial test based on Z-approximation reveals that observed proportion of patients with satisfactory- outcome was statistically significant (p = 0.05). Conclusion: This study concludes that Snodgrass urethroplasty has better cosmetic outcome. Thus we recommended it as the primary treatment for the children with distal hypospadias. Journal of Surgical Sciences (2014) Vol. 18 (1) : 9-14